2021
DOI: 10.1371/journal.ppat.1009794
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus biofilms: Toward understanding how growth as a multicellular network increases antifungal resistance and disease progression

Abstract: Aspergillus fumigatus is a saprophytic, filamentous fungus found in soils and compost and the causative agent of several pulmonary diseases in humans, birds, and other mammals. A. fumigatus and other filamentous fungi grow as networks of filamentous hyphae that have characteristics of a classic microbial biofilm. These characteristics include production of an extracellular matrix (ECM), surface adhesion, multicellularity, and increased antimicrobial drug resistance. A. fumigatus biofilm growth occurs in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 116 publications
0
19
0
2
Order By: Relevance
“…A. fumigatus biofilm formation is more resistant to antifungal agents (Morelli et al ., 2021). BRI alone at 20 or 40 µM can inhibit about 10 and 60% biofilm formation, respectively (Figure 2C) while VOR alone at 2 µg/ml or 4 µg/ml were able to inhibit about 10 and 50% biofilm formation (Figure 2C); CAS alone at 0.25 µg/ml or 2.0 µg/ml were able to inhibit about 10% biofilm formation (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…A. fumigatus biofilm formation is more resistant to antifungal agents (Morelli et al ., 2021). BRI alone at 20 or 40 µM can inhibit about 10 and 60% biofilm formation, respectively (Figure 2C) while VOR alone at 2 µg/ml or 4 µg/ml were able to inhibit about 10 and 50% biofilm formation (Figure 2C); CAS alone at 0.25 µg/ml or 2.0 µg/ml were able to inhibit about 10% biofilm formation (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Like biofilms in bacteria and yeast, the biofilms of A. fumigatus provide protection from antifungal therapy and host immune defenses 8 , 9 . Recent clinical trials highlight that the mortality of invasive aspergillosis remains as high as 30%, although treatment with the current antifungal agents 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The Candida biofilms consisted of a dense network of mixture morphological forms, including yeast cells, hyphae and pseudohyphae 15 . In comparison, interconnected, branched multinucleate vegetative hyphae are the main type of cells within A. fumigatus biofilms 8 . Three-dimensional surface plot analysis has revealed that spatially ordered hyphae, well-structured hyphal channels and vertical hyphal growth are characteristics of the A. fumigatus biofilms 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This makes it increasingly difficult for immune cells to recognise and influence them. It also worsens when other microbial biofilms persist and are difficult to remove with antifungal drugs, particularly in cystic fibrosis ( 111 ). Therefore, a comprehensive analysis and understanding of Aspergillus biofilms is required to develop new and improved antifungal targets for the treatment of complex biofilm-related diseases ( 107 ).…”
Section: Introductionmentioning
confidence: 99%